Where we belong: Chemehuevi and Caxcan preservation of sacred mountains - Ocampo, Daisy (The University of Arizona Press, 2023)
"This book examines the construction of memory in two indigenous sacred sites in the US and Mexico. It juxtaposes two relationships, the Chemehuevi people and their ties with the Old Woman Mountains of the East Mojave Desert, and the Caxcan people and their ties with Tlachialoyantepec in Zacatecas, Mexico. This research outlines a personal journey, a process of making connections through indigenous decolonial methodologies, and a research project in histories of both the Chemehuevi and Caxcan and their relationships to sacred mountains. This work emphasizes cultural engagements with performative and phenomenological insights as having historic preservation value"--